Occurrence of Limnophila Aquatica (Roxb.) Alston In Bangladesh - Alfasane, Md Almujaddade; Jolly, Jesmin Akhter; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2021)
Abstract not available Bangladesh J. Plant Taxon. 28(2): 455-457, 2021 (December)